1999
DOI: 10.1210/mend.13.9.0337
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-Mediated Proteolysis of Estrogen Receptor: A Novel Component in Autologous Down-Regulation

Abstract: Regulation of estrogen receptor (ER) concentration is a key component in limiting estrogen responsiveness in target cells. Yet the mechanisms governing ER concentration in the lactotrope cells of the anterior pituitary, a major site of estrogen action, are undetermined. In this study, we used a lactotrope cell line, PR1, to explore regulation of ER protein by estrogen. Estrogen treatment resulted in an approximate 60% decrease in ER steady state protein levels. Suprisingly, the decline in ER protein was appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
134
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(156 citation statements)
references
References 39 publications
19
134
1
2
Order By: Relevance
“…Therefore, this study used E-responsive breast cancer cell lines which express functional AhR and ER␣ as models for studying the mechanisms of AhR-dependent degradation of ER␣ through activation of proteasomes. Proteasome-dependent degradation of ER␣ is dependent on multiple factors, including ligand structure, cell context, and the form of ER␣ expressed (i.e., wild type, chimeric, or mutant) (2,11,29,52,54). For example, one study reported that ligand-mediated downregulation of ER␣ is linked to coactivator recruitment and coordinate degradation of both receptor and coactivator proteins in HeLa cells transfected with ER␣ or mutant ER␣ expression plasmids (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study used E-responsive breast cancer cell lines which express functional AhR and ER␣ as models for studying the mechanisms of AhR-dependent degradation of ER␣ through activation of proteasomes. Proteasome-dependent degradation of ER␣ is dependent on multiple factors, including ligand structure, cell context, and the form of ER␣ expressed (i.e., wild type, chimeric, or mutant) (2,11,29,52,54). For example, one study reported that ligand-mediated downregulation of ER␣ is linked to coactivator recruitment and coordinate degradation of both receptor and coactivator proteins in HeLa cells transfected with ER␣ or mutant ER␣ expression plasmids (29).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in various laboratories have demonstrated the implication of the ubiquitin-proteasome system (UPS) in the elimination of the mature receptor which has achieved transactivation and has become functionally obsolete (Alarid et al, 1999;El Khissiin, Leclercq, 1999;Laïos et al, 2005;Nawaz et al, 1999a;Wijayaratne, McDonnell, 2001). Natural and pharmacological ligands either accelerate (estrogens, pure antiestrogens) or reduce (partial antiestrogens) the proteasomal degradation of ERα (Laïos et al, 2005;Read et al, 1989;Wijayaratne, McDonnell, 2001) by selecting UPS with high or low degradation rate.…”
Section: Cam Contributes To the To Regulation Of Erα Turnover Ratementioning
confidence: 99%
“…MCF-7, IBEP-2), the steady-state level of the receptor is mostly determined by modulation of its degradation rate , Laïos et al 2003. As shown by studies employing specific inhibitors (El Khissiin & Leclercq 1999;Alarid et al 1999Alarid et al , 2006Lonard et al 2000;Journé et al 2004;Laïos et al 2005), ER breakdown involves the ubiquitinproteasome pathway. Modalities of ER degradation can, however, vary according to the receptor conformation, which is itself determined by the ligand-binding status and/or interactions with partner proteins , Tateishi et al 2004.…”
Section: Introductionmentioning
confidence: 99%